SOBRE-SEMEADURA DE FORRAGEIRAS HIBERNAIS EM PASTAGEM DEGRADADA DE PENSACOLA COM DOSES DE GLIFOSATO - Marçallo, Francisco Antonio (Scientia Agraria, 2003)
A field study was conducted at Fazenda Capão Redondo, near Candói - PR in southern Brazil, to evaluate the practice of overseeding cool-season forages on a degraded pasture of pensacola (Paspalum notatum Flügge var. Saurae) with and without glyphosate application for sod suppression. The specific objectives were to evaluate the contribution of cool-season forages to the pasture and the effect of glyphosate application on subsequent regrowth and botanical composition of the pensacola pasture. The study was conducted during 2000 and 2001 using a randomized complete block design with six treatments and two replications. A seed mixture of annual ryegrass (Lolium multiflorum Lam.), white clover (Trifolium repens L.), red clover (Trifolium pratense L.), and birdsfoot trefoil (Lotus corniculatus L.) was oversown on the pensacola pasture after dessication with different rates of glyphosate (T2=0; T3=O.5; T 4=0.75; T5=1.0; T6=1.25 L ha-1). The control treatment (T1) was the original pasture without herbicide, fertilizer, or overseeding treatments. The Botanal method was used to estimate the presence of each species in the available dry matter on four dates (8-Dec-2000, 9-Feb-2001, 6-Jun-2001, 20-Dec-2001). In the treatment without glyphosate, excellent establishment of winter forages was observed during the cold months followed by regrowth of pensacola in the summer. In the occurrence of hoar the glyphosate application was not necessary for successful establishment of the oversown species. Overseeding cool-season species in naturalized pastures, with or without glyphosate application, increased the proportion of high quality forages in the available dry matter during the winter, but reduced the presence of pensacola in the naturalized pasture the following summer. This practice also decreased the presence of native species in the pasture one year after overseeding. Presence of pensacola was inversely proportional to the presence of oversown species.